Increasing lengths of rank order lists of applicants and programs of US medical residencies. Issue 4 (April 2023) - Newsome, Kevin; Sen-Crowe, Brendon; Fanfan, Dino; McKenny, Mark; Elkbuli, Adel
Background: To match medical students into residency training programs, both the program and student create rank order lists (ROLs). We aim to investigate temporal trends in ROL lengths across 7 match cycles between 2014 and 2021 for both matched and unmatched residency applicants and programs. Methods: retrospective study of ROLs of 7 match cycles, 2014-2021. Residency match and ROL data were extracted from the NRMP database to assess the number of programs filled and unfilled, length of ROLs, position matched, and average ranks per position for osteopathic (DO) and allopathic (MD) medical programs. Results: For filled residency programs, the average ROL length consistently increased from 70.72 in 2015 to 88.73 in 2021 ( P = .003), with ROL lengths consistently longer for filled vs unfilled residency programs ( P < .001). The average ROL length for matched applicants increased consistently from 10.41 in 2015 to 12.35 in 2021 ( P = .002), with matched applicants having consistently longer ROLs than unmatched applicants ( P < .001). From 2015 to 2021, in both MD and DO applicants, progressively lower proportions of applicants matched their first and second choices. Conclusion: Trends across the past 7 residency match cycles suggest that ROL lengths for both programs and applicants have been increasing with matched programs and applicants submitting significantly longer ROLs than unmatched applicants. Additionally, fewer applicants are matching at their preferred programs over time. Our findings support the mounting evidence that the Match has become increasingly congested and we discuss the possible factors that may be contributing to the current state of the Match as well as potential solutions.